The Impact of Product and Service Quality on Consumer Loyalty at Bakso Adi in South Lampung - Dimas Aditya Saputra; Aida Sari (Management Dynamics: International Journal of Management and Digital Sciences, 2025)
This study examine the impact of product quality and service quality on consumer loyalty toward Bakso Adi, a local culinary business in Lampung, Indonesia. In recent years, consumers have become increasingly discerning, making product satisfaction and service experience crucial elements in shaping their loyalty. The research aims to examine how these two variables affect customer loyalty behavior, including repeat purchases, positive recommendations, and resistance to switching brands. The study employs a quantitative approach using a multiple linear regression model, with data collected through a questionnaire to 100 respondents (purposive sampling). The findings is both product quality and service quality significantly positively impact consumer loyalty. Product quality influences loyalty by meeting consumer expectations in taste and consistency, while service quality contributes through positive emotional experiences during customer interactions. These findings highlight the dual importance of maintaining high standards in both product and service aspects to retain customer trust and engagement. In conclusion, businesses like Bakso Adi must prioritize continuous improvement in product quality and service delivery to foster long-term customer loyalty. This study contributes to the understanding of loyalty formation in local food businesses and offers practical insights for customer retention strategies.